Analisis Penerapan Prosedur Audit Dana Kampanye Partai Politik Pada KAP Bambang Sutjipto Ngumar & Rekan - Gabrena Septi Aulia; Rida Perwita Sari (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This study provides an understanding of how the implementation of campaign finance audit procedures and evaluates its compliance with applicable regulations. The results showed that during the process of auditing campaign funds, KAP Bambang Sutjipto Ngumar & Rekan had implemented campaign fund audit procedures in accordance with the audit procedures and had submitted campaign fund audit reports in a timely manner to the KPU. This research also provides evaluation results to improve audit procedures, including increased auditor training and the development of more detailed audit guidelines. So that in general, the implementation of campaign finance audit procedures at KAP Bambang Sutjipto, Ngumar & Rekan has met the established audit quality standards.